Aging‐associated perifollicular changes and calcium deposition in poodles. Issue 1 (21st November 2018) - Miragliotta, Vincenzo; Buonamici, Sharon; Coli, Alessandra; Abramo, Francesca
Abstract : Background: It is commonly accepted that canine dystrophic mineralization of the hair follicle glassy membrane can be seen in hyperadrenocorticism and as a senile change in poodles. Pathology textbooks define this change as deposition of calcium salts in the form of basophilic, amorphous, granular material along collagen fibrils. Hypothesis/Objectives: The aim was to evaluate whether the incidence of the lesion is specific to poodles and if it is always associated with calcium deposition. Animals: One hundred and forty‐seven dogs divided into three groups: (i) 91 normal poodles; (ii) 40 dogs of other breeds; and (iii) 16 dogs with clinical/histopathological diagnosis of hyperadrenocorticism. Methods and materials: Retrospective study; with haematoxylin and eosin, and von Kossa staining. Results: Our findings demonstrate that perifollicular changes of the hair follicle glassy membrane of poodles are not always associated with calcium deposition. Conclusions and clinical importance: A specific staining is needed to identify true calcium deposition when performing histological examination of the skin of poodles. Abstract : Background – It is commonly accepted that canine dystrophic mineralization of the hair follicle glassy membrane can be seen in hyperadrenocorticism and as a senile change in poodles. Pathology textbooks define this change as deposition of calcium salts in the form of basophilic, amorphous, granular material along collagen fibrils.Hypothesis/Objectives – The aim was to evaluate whether the incidence of the lesion is specific to poodles and if it is always associated with calcium deposition.Conclusions and clinical importance – A specific staining is needed to identify true calcium deposition when performing histological examination of the skin of poodles.